Estudo fitoquímico e avaliação do potencial antioxidante in vitro dos frutos de Campomanesia ssp. - Ávila, Cristiane Maria dos Anjos de (2020)
The Cerrado has little-known and researched native fruits, contemplating possible sources of secondary metabolites with important phytochemical properties to be explored. Thus, this work sought to evaluate the scavenging capacity of DPPH, ABTS free radicals, reduction of the Phosphomolybdenum Complex and to quantify phenolic compounds, flavonoids, anthocyanins and total carotenoids in the aqueous extracts of the fruits of the plant species Campomanesia adamantium, C. guazumifolia, C. lineatifolia and C. sessiliflora found in the Cerrado in the Alto Paranaíba Region in Minas Gerais. The content of phenolic compounds was determined by the Folin-Ciocalteu method, total flavonoids and anthocyanins by Lees and Francis (1972) and total carotenoids by Lichtenthaler (1987). The C. guazumifolia extract showed higher levels of phenolic compounds (2,953.42 ± 141.22 mg EAG 100 g -1), flavonoids (43.17 ± 2.25 mg 100 g-1), anthocyanins (7.96 ± 0.38 mg 100 g-1), carotenoids (64.06 ± 12.55 mg g-1) and antioxidant activity by DPPH (568.3 mg EBHT g-1) and ABTS (105.3 mg EBHT g- 1), showing high antiradical potential in vitro. C. Adamantium also demonstrated significant results for phenolics (1,547.44 ± 79.49 mg EAG 100 g-1), flavonoids (36.63 ± 0.17 mg 100 g-1), anthocyanins (1.74 ± 0.10 mg 100 g-1), carotenoids (20.65 ± 0.43 mg g-1), DPPH (49.1 mg EBHT g-1), ABTS (83.7 mg EBHT g-1) and phosphomolybdenum complexation (105.1 mg EBHT g-1) showing a high reducing potential. Thus, the extracts of C. guazumifolia and C. adamantium are potentially promising for antioxidant activity and can be used in the prevention and treatment of pathologies related to oxidative stress.